Sensitivity of arabidopsis thaliana arp -/- mutants to genotoxic agents (Experimental biology, 2018)
Apurinic/apyrimidinic (AP) endonucleases are important DNA repair enzymes involved in two overlapping pathways: DNA glycosylase-initiated base excision (BER) and AP endonuclease-initiated nucleotide incision repair (NIR). In the BER pathway, AP endonucleases cleave DNA at AP sites and 3'-blocking moieties generated by DNA glycosylases, whereas in NIR, the same AP endonucleases incise DNA 5' to a wide variety of oxidized bases. The flowering plant Arabidopsis thaliana contains three genes encoding homologues of major human AP endonuclease 1 (APE1): Arp, Ape1L and Ape2. ARP is a major plant AP endonuclease that removes abasic sites. However, it was not known whether the plant AP endonucleases contain the NIR activity. Here, we report that homozygous A. thaliana arp–/– mutant exhibited high sensitivity to methyl methanesulfonate and tert-butyl hydroperoxide, but not to H2O2, suggesting that ARP-catalyzed NIR activity is required to repair AP sites generated by exogenous factors and specific oxidative DNA lesions induced by t-BuO 2H in vivo.  Extracts from arp–/– mutants, but not ape1L and ape2 mutants, exhibited no or very low NIR activity on the αdA•T. These results strongly suggest that ARP is a major AP site cleavage and NIR endonuclease in A. thaliana.
Keywords: AP endonuclease, A.thaliana, DNA glycosylases, reactive oxygen species (ROS).